Cenários de Insegurança: contributos do interaccionismo simbólico para uma análise sociológica da construção mediática do desvio - Paula Guerra (2002)
This report gives particular importance to symbolic interactionism as a theory explaining clipping and innovative in the explanation of the mechanisms of social domination. Specifically, we will give particular emphasis to the "importance of the media construction of social problems", noting that "to give a necessarily selective and certain privileging interpretations of the event, the press helps to make sense of these political and social movements with meanings, at the same time, overabundant and ambiguous. However, it would be too simple to see only the journalists as "handlers" who manufacture, for your pleasure, the events draw to review biased. They are themselves the subject of manipulation strategies by various social groups that organize demonstrations and look through them, to attract more or less success to the attention of journalists to have a chance of appearing in the media "(Champagne and others, 1998:222). This analysis option also allows us to discuss the applicability of the symbolic interactionism in the context of contemporary sociological research. Thus, we will make an application to social habitation of Porto based on systematic collection of news from two daily newspapers.